International Legal Aspects of Exercising Refugees' Rights in Central Asia - KHAMZIN, Amangeldy Shapievich; KHAMZINA, Zhanna Amangeldinovna; BURIBAYEV, Yermek Abiltayevich; TILEUBERGENOV, Yerazak Manapovich; IBRAIMOV, Dauren Akhmetzhanovich; YERMEKOV, Adlet Tokhtamysovich (Journal of Advanced Research in Law and Economics; Vol 7 No 4 (2016): JARLE, Volume VII, Issue 4(18), Summer 2016, 2016)
The relevance of this research is stipulated by theoretical and practical problems of international law on protecting refugees and exercising refugees’ rights in the countries of Central Asia. This problem has always attracted a lot of attention from the side of international organizations. Taking into account that in many countries human rights is one of the central issue in politics, refugees' rights and legislation on the national level in this sphere should be studied in further researches. All Central Asian countries, except Uzbekistan, joined the 1951 Refugee Convention and 1967 Protocol relating to the Status of Refugees, entering into an undertaking to protect those who needs protection. Later, the countries developed the laws on the national level, committing itself to define the status of refugees. The authors analyze the issues of legal regulation of the institute of asylum in Central Asia form the point of view of human rights; characteristics of politics and practices for granting of the refugee status in Central Asia are discussed; the author offers the way to optimize the process of solving theoretical and practical problems in exercising refugees' rights; recommendations to improve legislation in Central Asian countries relating to refugees' rights are suggested.